Technical Innovations and Complex Cases in Robotic Surgery for Lung Cancer: A Narrative Review - Giacomo Cusumano; Giuseppe Calabrese; Filippo Tommaso Gallina; Francesco Facciolo; Pierluigi Novellis; Giulia Veronesi; Stefano Viscardi; Filippo Lococo; Elisa Meacci; Alberto Terminella; Gaetano Romano; Cristina Zirafa; et al. (Current Oncology)
For over two decades, robotic-assisted thoracic surgery (RATS) has revolutionized thoracic oncology. With enhanced visualization, dexterity, and precision, RATS has reduced blood loss, shortened hospital stays, and sped up recovery compared to traditional surgery or video-assisted thoracoscopic surgery (VATS). The use of 3D high-definition imaging and articulated instruments allows for complex resections and advanced lymph node assessment. RATS delivers oncological outcomes similar to open surgery and VATS, with high rates of complete (R0) resections and acceptable complication rates. Its minimally invasive nature promotes quicker recovery. Advances in imaging software and augmented reality further enhance surgical accuracy and reduce intraoperative risks. However, RATS has some limitations, including high costs and a lack of tactile feedback, and certain complex procedures, such as extended resections and intrapericardial interventions, remain challenging. With growing experience and technological advances, RATS shows promise in reducing morbidity, improving quality of life, and expanding access to advanced oncologic care. This article reviews the evolution, benefits, and limitations of RATS in NSCLC treatment, highlighting its emerging role in managing complex cases.